2019
DOI: 10.3390/polym11030542
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Interface Properties on the Performance of Fiber-Reinforced Asphalt Binder

Abstract: This paper presents an experimental study about the influence of interfacial properties on the performance of fiber-reinforced asphalt. In this study, four types of fiber including one fiber-reinforced plastic (FRP), two lignin fibers, and one basalt fiber are used, and also four types of asphalt: Asphalt No. 90, asphalt No. 70, one styrene-butadiene-styrene (SBS) modified asphalt, and asphalt rubber are used. The surface energy parameters of various asphalts and fibers and the shear strength of various fiber-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 30 publications
1
24
0
1
Order By: Relevance
“…Asphalt modification technology has been considered a practical approach to resolve these concerns by enhancing the durability of asphalt pavements. Crumb rubber (CRM), styrene-butadiene-rubber (SBR) and styrene-butadiene-styrene (SBS) are the three most widely applied modifiers, which are regarded as effective adhesive and cohesive performance enhancers of asphalt [5][6][7][8][9]. However, the storage stability concern of modified asphalt has limited its widespread application.…”
Section: Introductionmentioning
confidence: 99%
“…Asphalt modification technology has been considered a practical approach to resolve these concerns by enhancing the durability of asphalt pavements. Crumb rubber (CRM), styrene-butadiene-rubber (SBR) and styrene-butadiene-styrene (SBS) are the three most widely applied modifiers, which are regarded as effective adhesive and cohesive performance enhancers of asphalt [5][6][7][8][9]. However, the storage stability concern of modified asphalt has limited its widespread application.…”
Section: Introductionmentioning
confidence: 99%
“…The test results revealed that OGFC with 0.2% basalt fiber and 4.5% SBS polymer had batter performances, and basalt fiber had a positive effect on reducing the draindown phenomenon. Miao et al [26] examined four types of fibers and four types of asphalt including neat asphalt and polymers modified asphalt based on the interfacial properties. The results indicated that basalt fiber had the prime reinforcement and SBS modified asphalt was found to be well reinforced with fiber.…”
Section: Introductionmentioning
confidence: 99%
“…Tanzadeh et al [ 25 ] investigated the open-graded friction course modified by polymer and basalt fiber by the drainage test and common mechanical test. Miao et al [ 26 ] examined four types of fibers (i.e., fiber-reinforced plastic, two lignin fibers, and basalt fiber) and four types of asphalt including neat asphalt and polymers-modified asphalt based on the interfacial properties. Luo et al [ 27 ] evaluated the enhancement impact of SBS and basalt fiber on the anti-rutting and anti-cracking of asphalt mixtures by the Hamburg wheel track test and low-temperature bending test, respectively.…”
Section: Introductionmentioning
confidence: 99%